Design and Performance of Ultraviolet 368-nm AlGaN-Based Flip-Chip High-Voltage LEDs with Epitaxial Indium Tin Oxide/Al Reflective Mirror and Symmetry Electrode Arrangement - Ma, Chuanzhe; Wang, Xinchang; Lao, Yuqin; Yang, Jiachen; Chen, Guojie; Wang, Gang; Fan, Bingfeng (Frontiers in Materials, 2022)
In this letter, we describe the design and fabrication of high-power AlGaN-based ultraviolet (UV) flip-chip high-voltage light-emitting diodes (LEDs) operating at 368 nm with an epitaxial indium tin oxide (ITO)/Al reflecting mirror and symmetry electrode layout. Metal-organic chemical vapor deposition (MOCVD) was used to grow an ITO thin film as a transparent electrode on the LED surface. At 365 nm, epitaxial ITO thin films exhibited a transmittance of up to 93.6%. Additionally, the epitaxial ITO/Al reflective mirror has a reflectance of 81.2% at 365-nm. To investigate the electrical characteristics, four types of HV-LED micro-cells were constructed with varying n-type mesa structures and p-type interconnect electrodes. We demonstrated a forward voltage (Vf) of 7.86 V at 350 mA with a 2×2 mico-cells high-voltage ultraviolet 368-nm flip-chip LED after optimising electrode structure and device process.